ANALISIS PERBEDAAN PERUBAHAN RISIKO SISTEMATIK DAN RISIKO OPERASIONAL SEBELUM DAN SESUDAH PENGGABUNGAN USAHA - WAHYU W, RESTI (Jurnal Akuntansi AKUNESA, 2015)
ABSTRACTBusiness combination is one of the strategies of the company to expand. These conditions would make changes to the risk of the company, that is systematic risk that comes from outside the company and operational risks that come from within the company. When the company merged two of these risks will be affected. This study aims to prove whether the right after the company merged change risks or not. Systematic risk is measured using a beta single index model and operational risk using the model of Altman Z-Score.The method used in this research was quantitative approach using non-parametric test Mann Whitney U test. Data was obtained from the Indonesia Stock Exchange (IDX), that was the company while merged from 2010 until 2013. Results of the study showed that the business combination did not affect the change of systematic risk and operational risk of the company. This means that there is no significant risk difference before and after the companies merged.Keywords : Business Combination, systematic risk, operational risk, beta, single index model, Altman Z-Score.